Effects of Business Process Management on Organisational Productivity: A Study of Selected Banks - Adeoye, Abayomi Olarewaju; Odusanya, Kafiu Sunkanmi (EuroEconomica, 2022)
This study investigated the effects of business process management on organisational productivity. The study adopted survey research design. The population of the study consisted of both male and female staff of Guaranty Trust Bank and United Bank of Africa. A sample size of two hundred and twenty-one (221) staff was selected. The study adopted Random Sampling Technique. Frequency description statistical method was used in analysing the data collected and all stated hypotheses were analysed using Pearson Correlation and the results revealed that there was a significant relationship between change in process and competitive advantage; also, the finding also revealed that there was a significant relationship between radical redesign and sales growth. The research therefore recommended that during the processes of reengineering, organizations should make frantic effort on their planning coupled with their strategies.